2019
DOI: 10.18632/aging.102362
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the patterns of cortical thickness in single- and multiple-domain amnestic mild cognitive impairment patients: a pilot study

Abstract: Amnestic mild cognitive impairment (aMCI) is considered as a transitional stage between the expected cognitive decline of normal aging and Alzheimer’s disease (AD). Structural brain difference has shown the potential in cognitive related diagnosis, however cortical thickness patterns transferred from aMCI to AD, especially in the subtypes of aMCI, is still unclear. In this study, we investigated the cortical thickness discrepancies among AD, aMCI and normal control (NC) entities, especially for two subtypes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
3
5
0
Order By: Relevance
“…The volume of the left fusiform gyrus in patients with mild cognitive impairment decreases with the development of the disease, accompanying the decline of cognitive function ( 36 38 ). This finding is consistent with the results of a previous study on cortical thickness ( 39 ). Our results showed that patients with SIVD had significant gray matter volume reductions in both the left and right fusiform gyruses compared with the NC.…”
Section: Discussionsupporting
confidence: 93%
“…The volume of the left fusiform gyrus in patients with mild cognitive impairment decreases with the development of the disease, accompanying the decline of cognitive function ( 36 38 ). This finding is consistent with the results of a previous study on cortical thickness ( 39 ). Our results showed that patients with SIVD had significant gray matter volume reductions in both the left and right fusiform gyruses compared with the NC.…”
Section: Discussionsupporting
confidence: 93%
“…To be more precise, both hemispheres of ERC thickness showed a decrease trend from HC to aMCI-s to aMCI-m to AD. These results add to the evidence that aMCI-m is more likely a transitional stage between aMCI-s and AD [5,6,17,31]. More importantly, our AUC results further proved that ERC thickness had superiority over ERC surface area and volume in discriminating among the four groups.…”
Section: Discussionsupporting
confidence: 79%
“…To date, it is still unclear how ERC thickness, volume and surface area changes among AD, aMCI and HC entities, especially for aMCI subtypes (aMCI-s and aMCI-m). In addition, different morphological indexes have been proven to be affected differently in the course of disease [13,16] and cortical thickness and volume were demonstrated to have differentials among AD, aMCI and healthy controls in distinct cortical regions [17]. Therefore, combining multiple morphological indexes may effectively reveal subtle structural alterations in the early stage of AD and improve classi cation accuracy of aMCI subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…To be more precise, both hemispheres of ERC thickness showed a decreasing trend from HC to aMCI-s to aMCI-m to AD. These results add to the evidence that aMCI-m is more likely a transitional stage between aMCI-s and AD [ 5 , 6 , 17 , 31 ]. More importantly, our AUC results further prove that ERC thickness has superiority over ERC surface area and volume in discriminating among the four groups.…”
Section: Discussionsupporting
confidence: 72%
“…To date, it is still unclear how ERC thickness, volume and surface area change among AD, aMCI and HC entities, especially for aMCI subtypes (aMCI-s and aMCI-m). In addition, different morphological indexes have been proven to be affected differently in the course of disease [ 13 , 16 ], and cortical thickness and volume were demonstrated to have differences among AD, aMCI and healthy controls in distinct cortical regions [ 17 ]. Therefore, combining multiple morphological indexes may effectively reveal subtle structural alterations in the early stage of AD and improve classification accuracy of aMCI subtypes.…”
Section: Introductionmentioning
confidence: 99%